Jatanā: A Peasant Woman's Ballad from Haryana in North India. Issue 1 (2nd January 2017) - Kumar, Devender
Abstract: Women's private folk songs in male-dominated societies often keep a fascinating record of their critique of the patriarchy's hegemonic tendencies. These folk songs reveal the women's sense of resentment against their subordinated position in a patriarchal system, and also their desire to live in an egalitarian world. This article analyses a North Indian Haryanvi peasant women's folk ballad called Jatanā as a site of both resentment against masculinist culture and imaginative and defiant escape from its bounds.